Offshore outsourcing - A global shift in the present IT industry - Georg Erber; Aida Sayed-Ahmed (Universität Hohenheim, 2004)
The paper analyses the offshore outsourcing of IT services (OOIT), which have become increasingly important for the global IT industry. Through this rapid process of firm relocation, a new terminology has emerged, which forms the starting point for our paper. We compare wage cost differentials of IT workers in key offshore locations like India to those in the US and Europe, incorporating the hidden costs of offshoring - including long-term risks and opportunities - in order to determine the total cost of offshore outsourcing activities. The debate on the potential future negative employment impacts in the major OECD countries recently became a point of political contention in the US presidential election campaign, reflecting widespread fears in the US and elsewhere that outsourcing will lead to decreased income and job loss. In Europe, policy makers are searching for instruments to guide these developments so that major social disruptions do not lead to disproportionately negative welfare impacts in the short term. The future costs and benefits of outsourcing can currently be assessed only in broad terms due to the lack of adequate data and representative statistics. However, the theory of comparative advantages suggests that overall, offshoring and inshoring countries will gain from the new international division of labour in the long run.
urn:nbn:de:bsz:100-opus-4500
Keywords: F16; F21; F23; 330; offshore outsourcing of IT; international factor movements and labour markets; international business; multinational firms